LAYANAN PENDIDIKAN AGAMA BUDDHA DI KABUPATEN TULANG BAWANG BARAT PROVINSI LAMPUNG: STUDI KASUS SISWA BERAGAMA BUDDHA DI SEKOLAH FORMAL - Alim, Inung Kurnia Alim; Sulani, Puji Sulani; Parjono, Parjono (Jurnal Pencerahan, 2024)
This case study aims to analyze Buddhist religious education services in Tulang Bawang Barat Regency, Lampung Province, particularly for students who do not receive Buddhist Religious Education in formal schools. This research uses a qualitative approach with a case study method, with data collection conducted through observation, interviews, and documentation assisted by data collection guidelines. The data validity is ensured through credibility, transferability, dependability, and confirmability criteria. Data analysis is performed using the Miles, Huberman, and Saldaña model, including stages of data collection, condensation, presentation, and conclusion/verification. The research findings show that the number of Buddhist students in Tulang Bawang Barat Regency is relatively small, and their right to receive Buddhist religious education services has not been fully met. Furthermore, there is only one Buddhist religious teacher with a bachelor's degree in the regency. The Buddhist religious education services received by the students include attending Buddhist lessons from a Buddhist teacher, attending other religious lessons but receiving Buddhist material from a classroom teacher or another religious teacher, and not receiving Buddhist religious education services. Several parties have attempted to find solutions by providing training and development for Buddhist teachers and Sunday School organizers, seeking new Buddhist teachers, and providing materials from the Vihara with available books. In addition, coordination with Buddhist teachers and the communication of issues through parent-teacher meetings have also been carried out.